2021
DOI: 10.1177/00037028211032930
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis Aided Surface-Enhanced Raman Spectroscopy (MVA-SERS) Multiplex Quantitative Detection of Trace Fentanyl in Illicit Drug Mixtures Using a Handheld Raman Spectrometer

Abstract: Recently there has been upsurge in reports that illicit seizures of cocaine and heroin have been adulterated with fentanyl. Surface-enhanced Raman spectroscopy (SERS) provides a useful alternative to current screening procedures that permits detection of trace levels of fentanyl in mixtures. Samples are solubilized and allowed to interact with aggregated colloidal nanostars to produce a rapid and sensitive assay. In this study, we present the quantitative determination of fentanyl in heroin and cocaine using S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Moreover, the NS/ CO 3 2− (c) formulation has already been successfully applied to the detection of such a class of analytes, both in standard solutions 85 and in binary mixtures of other abused substances. 86 While the effects of nanoparticle morphology are commonly reported in the literature, comparisons of different surface environments are less frequently explored. In our case, the effect of the surface environment was deemed more important than that of shape, encouraging further exploration of surface chemistry in the optimization of SERS-based analytical protocols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the NS/ CO 3 2− (c) formulation has already been successfully applied to the detection of such a class of analytes, both in standard solutions 85 and in binary mixtures of other abused substances. 86 While the effects of nanoparticle morphology are commonly reported in the literature, comparisons of different surface environments are less frequently explored. In our case, the effect of the surface environment was deemed more important than that of shape, encouraging further exploration of surface chemistry in the optimization of SERS-based analytical protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Although these foundational experiments were all conducted utilizing CV as an ideal SERS probe, the superiority in performance was also verified with nonideal probes, such as the opioids acrylfentanyl and benzylfentanyl (Supporting Information). Moreover, the NS/CO 3 2– (c) formulation has already been successfully applied to the detection of such a class of analytes, both in standard solutions and in binary mixtures of other abused substances . While the effects of nanoparticle morphology are commonly reported in the literature, comparisons of different surface environments are less frequently explored.…”
Section: Discussionmentioning
confidence: 99%
“…To detect fentanyl in heroin at concentrations as low as 0.05% with a portable instrument, Wang et al even developed a SERS method. 211 A limit of detection for fentanyl as low as 0.001% was achieved by Wilson et al using portable SERS, and they identified fentanyl in mixtures with heroin and caffeine, a common diluent. 212 Gozdzialski et al illustrated the advantages of SERS over current immunoassay strips well.…”
Section: ■ Chemistry: Seized Drugs and Toxicologymentioning
confidence: 99%
“…Using a hand-held Raman spectrometer, Wang et al quantified fentanyl in illicit drug mixtures. 12 Mirsafavi et al utilized SERS to detect and classify fentanyl and its precursors. 217 These papers pave the way for the creation of a portable spectral library that would contain spectral information for fentanyl and its precursors.…”
Section: Commercialization Of Forensic Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation